Adopting Cross-Dressing: A Strategy for Coping with Loss for a Bisexual Man - Abidah R. Delu; Budiawan (Soshum: Jurnal Sosial dan Humaniora, 2024)
Cross-dressing refers to the act of donning garments often associated with the opposite gender. Throughout history, cross-dressing has been extensively recorded and is frequently linked to stereotypes such as deviance, fetishism, exhibitionism, sexual deviance, and homosexuality. Coping mechanisms refer to psychological strategies employed by the subconscious mind to shield individuals from feelings of anxiety, social repercussions, and unmanageable circumstances in the immediate present. This study aimed to elucidate that Cross-Dressing is not just attributable to perceptions of sexual deviance and transvestism, but rather, other factors contribute to an individual's adoption of Cross-Dressing. The research methodology employed in this study is a single-design case study. The study found that the participants experienced the loss of their beloved mother as a catalyst for adopting a Cross-Dressing lifestyle, perceiving it as a means to compensate for the void created by her death. The findings of this study indicate that cross-dressing behaviour serves as a long-lasting method for individuals to repress their emotions related to loss rather than being primarily attributed to transvestism or preconceptions of sexual deviance associated with the subject of investigation.